Proposed new interior design scheme of Extreme Sports Equipment and Protective Gear Store for Sunway City Extreme Park at Lot 16, Festival Walk, Medan Ipoh Bistari, Ipoh / Muhammad Zamri Mohd Janin - Mohd Janin, Muhammad Zamri (Faculty of Architecture, Planning and Surveying, 2012)
This project is about proposing new interior design scheme of Extreme Sports Equipment and Protective Gear Store for Extreme Park Sdn Bhd at lot 16, Festival Walk, Persiaran Medan Ipoh, Medan Ipoh Bistari, Ipoh. The total interior area is 3360 sq. ft. The idea of proposing a store is to provide a complete facilities to consumers especially fans of extreme sports to get their needed equipment and protective gear and at the same times to try out new activities that are rarely performed. The site located in Medan Ipoh, Ipoh. It is near to Jusco and Ipog Garden Mall, and besides to the Tesco. This location is very strategic because it is in hot spot of Bandar Ipoh which center to residential, commercial area, recreation park, education and most important full of facilities either public transportation or safetynesss. This project was followed by a few stages of progress. Every stages is include with presentation. The stages goes by proposal stage then followed by planning stage and lastly final presentation. The project is completed when all this stages complete.